STI Co-infection Among HIV/AIDS Patients at H. Adam Malik General Hospital, Medan, Indonesia - Khairuna, Safirah (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
Both HIV/AIDS and Sexually Transmitted Infection (STI) are transmitted through sexual activites making a parallel port of entry making the two condition  increase the each other’s transmission which results as an impact to progression of HIV infection. This study aims to determine the characteristics of HIV/AIDS patients co-infected with sexually transmitted infections in H. Adam Malik General Hospital Medan between 2017 and 2018. This study is a descriptive observational study of 2422 HIV/AIDS patients attending H. Adam Malik General Hospital. Of those, 62 patients were diagnosed with STI coinfection. The majority of patients were male (85,5%) aged within the group of 25 – 49 years old (80,6%), had the level education of high school (88,7%), mostly were entrepreneurs (50%), and were single (59,7%). Most of the patients were already in their Stadium III (80,6%) clinical stage and had CD4+ count < 200/mm3 (51,6%). Condyloma acuminatum (35,5%) was found as the most common type of STI coinfection, and followed by Hepatitis B (33,9%).Based on anamnesis history, behavioral risk factors (66,1%) was the most frequent risk    factor